2022
DOI: 10.1002/tox.23651
|View full text |Cite
|
Sign up to set email alerts
|

Xiaotansanjiefang inhibits the viability of colorectal cancer cells via Jagged 1/Notch 3/Snail signaling pathway

Abstract: The purpose of this study is to explore the anti‐colorectal cancer of Xiaotansanjiefang, a famous traditional Chinese medicine, and its potential anti‐cancer mechanism. In this study, the HCT116 cell spheres were prepared as in vitro study model. We found the Xiaotansanjiefang medication was able to inhibit the proliferation of HCT116 cell spheres in a dose‐dependent manner, especially in 3 and 6 mg/ml Xiaotansanjiefang medication treated groups. We also found the high concentration of Xiaotansanjiefang medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, NOTCH3 ICD might interfere with NOTCH1-mediated activation of HES1 by competing with the NOTCH1 ICD to access the RBP-Jk transcriptional factor modulated by the Notch pathway (Beatus et al, 1999), and by competing for a common activator, DLL4 (Serafin et al, 2011) (Figure 3). This inhibition of the HES1 activation by NOTCH3 might be circumstantial though, since several in vitro and in vivo studies demonstrated the activation of HES1 by NOTCH3 (Bellavia et al, 2000;Shimizu et al, 2002;Ye et al, 2022).…”
Section: Notch Ligand-receptor Specificity and Colorectal Cancer Stem...mentioning
confidence: 96%
“…However, NOTCH3 ICD might interfere with NOTCH1-mediated activation of HES1 by competing with the NOTCH1 ICD to access the RBP-Jk transcriptional factor modulated by the Notch pathway (Beatus et al, 1999), and by competing for a common activator, DLL4 (Serafin et al, 2011) (Figure 3). This inhibition of the HES1 activation by NOTCH3 might be circumstantial though, since several in vitro and in vivo studies demonstrated the activation of HES1 by NOTCH3 (Bellavia et al, 2000;Shimizu et al, 2002;Ye et al, 2022).…”
Section: Notch Ligand-receptor Specificity and Colorectal Cancer Stem...mentioning
confidence: 96%
“…Accumulating evidence indicated that melatonin, 11 dichlorodiphenyltrichloroethane, 12 xiaotansanjiefang, 13 traditional Chinese medicine formula T33, 14 and some active ingredients and extracts of traditional Chinese medicine, such as xanthohumol, 15 hinokitiol, 16 bergapten, 17 lupeol, 18 tribulus terrestris fruit extract, 19 momordica balsamina crude acetone extract, 20 and crude extract of Rheum palmatum L 21,22 showed the anti‐cancer activity in colorectal cancer. In addition, the leguminous plant sophora flavescens has been used for more than 2000 years, as a traditional Chinese medicine, and matrine, an alkaloid, was extracted from it and exerted multiple pharmacological effects, such as antiviral, diuretic, anti‐inflammatory and anti‐allergic effects 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the most common malignancy in both men and women, and the second leading cause of cancer-related death worldwide (1). Poor diet, lack of physical activity, obesity, drinking alcoholic beverages, and cigarette smoking are risk factors for CRC formation (2,3).…”
mentioning
confidence: 99%